The group 13 metal complexes of sterically-hindered substituted iminophenol: synthesis and structure. Issue 25 (21st March 2015) - Egorova, Elena N.; Druzhkov, Nikolay O.; Shavyrin, Andrey S.; Cherkasov, Anton V.; Abakumov, Gleb A.; Fedorov, Alexey Yu
<x xml:space="preserve">Abstract</x> The synthesis of complexes I–IV.